2023
DOI: 10.1186/s13073-023-01240-0
|View full text |Cite
|
Sign up to set email alerts
|

Structural and non-coding variants increase the diagnostic yield of clinical whole genome sequencing for rare diseases

Alistair T. Pagnamenta,
Carme Camps,
Edoardo Giacopuzzi
et al.

Abstract: Background Whole genome sequencing is increasingly being used for the diagnosis of patients with rare diseases. However, the diagnostic yields of many studies, particularly those conducted in a healthcare setting, are often disappointingly low, at 25–30%. This is in part because although entire genomes are sequenced, analysis is often confined to in silico gene panels or coding regions of the genome. Methods We undertook WGS on a cohort of 122 unre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 123 publications
0
6
0
Order By: Relevance
“…6/33 patients (18%) were referred with genetically undefined T − B + NK + SCID requiring further investigations before deciding the most appropriate corrective procedure, HSCT or TT. These investigations included broader genetic testing with agnostic analyses [ 60 , 61 ] and diagnostic research assays to test the ability of their CD34 + haematopoietic stem and progenitor cells to differentiate into CD3 + T lymphocytes in vitro to help distinguish haematopoietic cell-intrinsic defects from thymic defects [ 62 64 ]. Overall, 18/33 patients were accepted for TT and 2/33 underwent HSCT.…”
Section: Resultsmentioning
confidence: 99%
“…6/33 patients (18%) were referred with genetically undefined T − B + NK + SCID requiring further investigations before deciding the most appropriate corrective procedure, HSCT or TT. These investigations included broader genetic testing with agnostic analyses [ 60 , 61 ] and diagnostic research assays to test the ability of their CD34 + haematopoietic stem and progenitor cells to differentiate into CD3 + T lymphocytes in vitro to help distinguish haematopoietic cell-intrinsic defects from thymic defects [ 62 64 ]. Overall, 18/33 patients were accepted for TT and 2/33 underwent HSCT.…”
Section: Resultsmentioning
confidence: 99%
“…Next-generation-based DNA sequencing strategies are already established in the clinical practice of rare diseases including overgrowth syndromes ( Pagnamenta et al, 2023 ), however gene expression data are hardly utilized in routine clinical practice. A recent exploratory study has demonstrated the potential for gene expression profiling to aid in both, the diagnosis and classification of a disease entity.…”
Section: Discussion/perspectivesmentioning
confidence: 99%
“…Although copy-number changes in exome sequencing can be used to infer deletions, it can be challenging to draw conclusions, especially in homologous regions like CLCNKA and CLCNKB. WGS theoretically has a higher ability to identify a more diverse spectrum of variant profiles, including deep intronic, regulatory, andSVs, compared to exome sequencing [25]. Accordingly, its coverage includes the findings of all other genomic approaches.…”
Section: Discussionmentioning
confidence: 99%